ASUHAN KEBIDANAN POST SECTIO CAESARIA PADA NY. I DENGAN PREEKLAMPSIA BERAT DI RSUD SEKARWANGI - Agni Saila Rizqiah; Sri Wahyuni; Ni Wayan Dian Ekayanthi; Ni Nyoman Sasnitiari (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
Maternal Mortality Rate (MMR) according to the Indonesian Demographic and Health Survey (IDHS) in 2017 is still high at 305 per 100,000 live births, namely 1,712 cases in 2017 live births.The purpose of this Final Project Report is to apply midwifery care to deal with problems in Ny. I post sectio caesaria with severe pre-eclampsia at Sekarwangi Regional Hospital.The method used is a case report with SOAP documentation. Subjective data obtained by the mother says she still feels weak, slightly dizzy, and feels pain in the post-operative wound. Objective data of blood pressure 160/100 mmHg, abdominal surgery, hard and globular contractions, 1 finger TFU below the center, lower extremities in both legs of edema, genetalia vulva and vagina no abnormalities, lochea rubra, the amount is within normal limits. Analysis established by Ny.I at 21 years of age P1A0 Post sectio cesaria with severe preeclampsia. Management is TTV observation, contraction, bleeding, post-SC care, collaborating with doctors and then mothers are given mefenamic acid therapy 1 amp IV and Dopamet 3x500 mg and continue to monitor the rate of MgSO4 infusion with the conditions of administration ie breathing> 16x / min, urine production > 30cc / hour, patella + reflex, and calcium gluconate antidote available. The conclusion is that the mother's condition is improving and the mother is allowed to go home on February 11, 2020. Suggestions for clients and families is that clients and families can find out the right management for post sectio caesarean mothers with severe preeclampsia